Puzzling parrotfishes: Radiocarbon age validation and updated longevity estimates for western Atlantic species in support of sustainable fisheries management - Hernandez, Jesus M. Rivera; Shervette, Virginia R. (PLOS ONE, 2024)
For management efforts to succeed in Caribbean fisheries, local fishers must support and be willing to comply with fishing regulations. This is more likely when fishers are included in a stock assessment process that utilizes robust scientific evidence, collected in collaboration with fishers, to evaluate the health of fish stocks. Caribbean parrotfishes are important contributors to coral reef ecosystem health while also contributing to local fisheries. Scientifically robust stock assessments require regional species-specific information on age-based key life history parameters, derived from fish age estimates. Evaluation of the accuracy of age estimation methods for fish species is a critical initial step in managing species for long-term sustainable harvest. The current study resulted from a collaborative research program between fish biologists and local fishers investigating age, growth, and reproductive biology of the seven parrotfish species landed in U.S. Caribbean fisheries; specifically, we validated age estimation for stoplight parrotfish Sparisoma viride and queen parrotfish Scarus vetula. This is the first study to directly validate age estimation for any parrotfish species through analysis of Δ14C from eye lens cores. Our age estimation validation results show that enumeration of opaque zones from thin sections of sagittal otoliths for a Sparisoma and a Scarus species provides accurate age estimates. The oldest stoplight parrotfish and queen parrotfish in the Δ14C age estimation validation series were 14 y and 16 y; while the oldest stoplight parrotfish and queen parrotfish we aged to-date using the Δ14C validated age estimation method were 20 y and 21 y, respectively. Fish longevity (maximum age attained/life span) is a key life history parameter used for estimation of natural mortality, survivorship, and lifetime reproductive output. Past reviews on parrotfishes from the Pacific and Atlantic concluded that most Caribbean/western Atlantic parrotfish species are relatively short-lived with estimated maximum ages ranging from 3–9 y. However, information from our collaborative research in the U.S. Caribbean combined with recently published age estimates for Brazilian parrotfish species indicate that many western Atlantic parrotfishes are relatively long-lived with several species attaining maximum ages in excess of 20 y.
Publisher: Public Library of Science
Keywords: Caribbean; coral reefs; Eye lens; Fish biology; Fisheries; Marine fish; Otolith; Spawning

Caribbean deepwater snappers: Application of the bomb radiocarbon age estimation validation in understanding aspects of ecology and life history - Overly, Katherine E.; Shervette, Virginia R. (PLOS ONE, 2023)
Reef fishes have been utilized as food fish throughout the U.S. Caribbean and Gulf of Mexico waters for centuries, with increasing fishing effort in recent decades. As a result, many species have experienced declines in landings, including deepwater snappers such as queen snapper Etelis oculatus and blackfin snapper Lutjanus buccanella. However, little to no peer-reviewed published research exists on basic life history parameters for either species. Confirming the accuracy of an age estimation method for a fish species is essential for ensuring sustainable fisheries management. This is because in the assessment of fisheries species population age-based parameters, including longevity, age at sexual maturity, growth rate, mortality, age-specific reproductive output, and lifetime reproductive output, are important in understanding overall life history strategies of managed stocks. The past stock assessment on U.S. Caribbean queen snapper utilized an estimated longevity of 8 y, derived from length frequencies for fish from St. Lucia. Blackfin snapper has an estimated longevity of 27 y based on a relatively small study from offshore waters of the southeastern U.S. The focus of our investigation was to estimate maximum longevity of two data-poor species in the U.S. Caribbean. The accuracy of ageing methods was tested via bomb radiocarbon age estimation validation and effects of depth on Δ14C in otolith cores and eye lens core values were examined. Results from our work indicate a maximum validated age of 45 y for queen snapper, and 43 y for blackfin snapper. Our findings indicate queen snapper and blackfin snapper are long-lived (> 40 y). The resulting Δ14C comparison between eye lens cores and otolith cores has important implications for the study of age validation, specifically when deepwater species are involved.
Publisher: Public Library of Science
Keywords: Caribbean; Eye lens; Eyes; Fisheries; Larvae; Marine fish; Otolith; Reefs

Queen triggerfish Balistes vetula: Validation of otolith-based age, growth, and longevity estimates via application of bomb radiocarbon - Shervette, Virginia R.; Rivera Hernández, Jesús M. (PLOS ONE, 2022)
Ensuring the accuracy of age estimation in fisheries science through validation is an essential step in managing species for long-term sustainable harvest. The current study used Δ14 C in direct validation of age estimation for queen triggerfish Balistes vetula and conclusively documented that triggerfish sagittal otoliths provide more accurate and precise age estimates relative to dorsal spines. Caribbean fish samples (n = 2045) ranged in size from 67-473 mm fork length (FL); 23 fish from waters of the southeastern U.S. (SEUS) Atlantic coast ranged in size from 355-525 mm FL. Otolith-based age estimates from Caribbean fish range from 0-23 y, dorsal spine-based age estimates ranged from 1-14 y. Otolith-based age estimates for fish from the SEUS ranged from 8-40 y. Growth function estimates from otoliths in the current study (L∞ = 444, K = 0.13, t0 = -1.12) differed from spined-derived estimates in the literature. Our work indicates that previously reported maximum ages for Balistes species based on spine-derived age estimates may underestimate longevity of these species since queen triggerfish otolith-based ageing extended maximum known age for the species by nearly three-fold (14 y from spines versus 40 y from otoliths). Future research seeking to document age and growth population parameters of Balistes species should strongly consider incorporating otolith-based ageing in the research design.